CYBERBULLYING: VIOLENCE IN THE DIGITAL WORLD (Heritage, 2024)
The appearance of cyberbullying in the digital age is a serious social problem that requires careful study and an adequate approach to its prevention. This paper analyzes the definition of cyberbullying, its characteristics, causes and consequences of this phenomenon. The progress of information and communication technologies, accompanied by the growing accessibility of the Internet, has resulted in the emergence of new forms of education, communication and entertainment. However, at the same time, the door opens to new opportunities for violent behavior. The continuous development of technology has transformed the way people interact, creating new digital spaces in which a wide range of activities take place. In such an environment, phenomena such as cyberbullying, online abuse, identity theft and other digital threats have become more and more present, at the same time causing concern to society, which results in the need for an adequate prevention and response strategy. Cyberbullying can be defined as intentional abuse or harassment of an individual through social networks, e-mail, phone calls or messages, electronic media, which is repeated over time. Considering the ubiquity of digital communication as an everyday interaction in society, a more detailed understanding of how digital violence can cause serious mental, emotional and social consequences for all exposed persons is necessary. Digital violence can be manifested in a variety of ways, not limited to cyberbullying, threats via the Internet, distribution of inappropriate content, and the like. The above mentioned types of abuse can cause permanent and deep traumas, reduce the level of self-confidence of people who are labeled with this type of violence, damage them emotionally and socially. This paper provides a broader picture of the impact of digital violence on all aspects of personality with a special emphasis on the identification of risk factors and the development of prevention with the aim of protecting each individual in the digital environment.
Keywords: cyberbullying, violence, digital world, emotions